Elevation of preoperative cystatin C as an early predictor of contrast-induced nephropathy in patients receiving percutaneous coronary intervention - Guoqiang Gu; Ningning Yu; Yaqing Zhou; Wei Cui (Singapore Medical Journal)
Introduction: Contrast-induced nephropathy (CIN) is a serious complication of percutaneous coronary intervention (PCI). The most important predictor of CIN is renal function before PCI. Serum creatinine (SCr) is a commonly used biomarker of renal function, but an elevation in SCr lags behind the onset of kidney injury and is not viable for early detection of CIN after PCI. Our primary objective was to investigate whether preoperative cystatin C (CysC) before PCI was an early predictor of postoperative CIN. The secondary objective was to evaluate associations between preoperative CysC and renal biomarkers. Methods: From December 2014 to December 2015, 341 patients with normal renal function were enrolled into the study at our medical centre. All patients were apportioned to normal CysC (≤1.03 mg/L) or high CysC (>1.03 mg/L) groups before PCI and were hydrated from four hours prior to PCI to 24 hours after it. Renal function was monitored at 48 hours after PCI. Clinical parameters were recorded before and after PCI. Results: There was no significant difference in preoperative SCr between the CIN and non-CIN groups. However, preoperative CysC demonstrated significant difference between the two groups (p <0.01). Logistic regression analysis showed that elevated CysC before PCI was a risk factor for CIN (p = 0.013). Furthermore, the linear regression models identified an association between CysC before PCI and renal function after PCI. Conclusion: CysC before PCI was viable as a biomarker of renal function after PCI and high preoperative CysC was able to predict CIN earlier than SCr.